The regulation of gambling : European and national perspectives - Littler, Alan; Fijnaut, Cyrille, 1946- (Martinus Nijhoff, 2007)
In November 2005, Tilburg University hosted an international Colloquium on the European and National Perspectives of the Regulation of Gambling. This book reflects the results of this day and brings together a range of perspectives from the contemporary debate surrounding the regulation of gambling markets within the context of the European Union.